2013
DOI: 10.1371/journal.pone.0057090
|View full text |Cite
|
Sign up to set email alerts
|

A C. trachomatis Cloning Vector and the Generation of C. trachomatis Strains Expressing Fluorescent Proteins under the Control of a C. trachomatis Promoter

Abstract: Here we describe a versatile cloning vector for conducting genetic experiments in C. trachomatis. We successfully expressed various fluorescent proteins (i.e. GFP, mCherry and CFP) from C. trachomatis regulatory elements (i.e. the promoter and terminator of the incDEFG operon) and showed that the transformed strains produced wild type amounts of infectious particles and recapitulated major features of the C. trachomatis developmental cycle. C. trachomatis strains expressing fluorescent proteins are valuable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 53 publications
(53 reference statements)
1
122
0
Order By: Relevance
“…Such events might occur within the confines of infected epithelial cells, and several studies have demonstrated that more than one C. trachomatis strain can simultaneously infect the same cell and form a single mixed intracellular inclusion (20,141,142). Once inside the host cell, coinfecting strains may exchange DNA, presumably while coinhabiting the same inclusion, although inclusion fusion might not be an absolute requirement for DNA exchange, because C. trachomatis isolates with nonfusogenic inclusions can exchange DNA in vitro (143).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such events might occur within the confines of infected epithelial cells, and several studies have demonstrated that more than one C. trachomatis strain can simultaneously infect the same cell and form a single mixed intracellular inclusion (20,141,142). Once inside the host cell, coinfecting strains may exchange DNA, presumably while coinhabiting the same inclusion, although inclusion fusion might not be an absolute requirement for DNA exchange, because C. trachomatis isolates with nonfusogenic inclusions can exchange DNA in vitro (143).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%
“…1 and 2). For example, the plasmid p2TK2-SW2 (20) and the pBOMB4 series of plasmids (21) combined a ␤-lactamase-encoding gene (bla) and a multiple-cloning site into the L2 pSW2 and pL2 (L2/434/Bu) plasmids, respectively. The pBOMB4 series offers the additional benefit of utilizing an intact L2 plasmid (pL2) rather than the SW2 variant plasmid, which harbors a 377-bp deletion in CDS1 (148).…”
Section: Ectopic Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel application of this approach is for derivation of meaningful quantitative data about the inclusion, for example inclusion area, volume and shape. Finally, this visualization method is highly adaptable and can be used in combination with other fluorescent markers to reveal additional insight into the biology of Chlamydia infected host cells, for example GFP-or mKate2-expressing Chlamydia 6,11 , fluorescent actin 12 or GFP tagged Inc proteins 13 .…”
Section: Discussionmentioning
confidence: 99%
“…One of these limitations was removed when a novel method for introducing DNA and modificating the native plasmid to allow effective selection of transformants has enabled the development of key molecular tools for studying Chlamydia. This transformation system was employed to test the expression of a diverse set of fluorescent proteins and to demonstrate the utility of subcellular localization studies [52]. The C. trachomatis developmental cycle incorporates numerous poorly understood processes, but a method for transforming Chlamydia has recently enabled the development of essential molecular tools to better study the biology and pathogenesis of these bacteria.…”
Section: Determining the Antibiotics Resistance Of Pathogen Std Agentsmentioning
confidence: 99%